Antiproliferative effects of metformin in cellular models of pheochromocytoma. (1st January 2022) - Meireles, Cinthia Gabriel; Lourenço de Lima, Caroline; Martins de Paula Oliveira, Marcela; Abe da Rocha Miranda, Rafael; Romano, Lisa; Yo-Stella Brashaw, Teisha; Neves da Silva Guerra, Eliete; de Assis Rocha Neves, Francisco; Chapple, J. Paul; Simeoni, Luiz Alberto; Lofrano-Porto, Adriana
Abstract: Pheochromocytomas (PCCs) are rare neuroendocrine tumors derived from adrenal medulla chromaffin cells. Malignancy and recurrence are rare but demand effective treatment. Metformin exerts antiproliferative effects in several cancer cell lines. We thus evaluated the effects of metformin on cell viability and proliferation, cellular respiration and AMPK-AKT-mTOR-HIFA proliferation pathway on a rat PCC cell line (PC12-Adh) . We then addressed metformin's effects on the AMPK-AKT-mTOR-HIFA pathway on two human primary cultures: one from a VHL-mutant PCC and other from a sporadic PCC. Metformin (20 mM) inhibited PC12-Adh cell proliferation, and decreased oxygen consumption, ATP production and proton leak, in addition to loss of mitochondrial membrane potential. Further, metformin induced AMPK phosphorylation and impaired AMPK-PI3k-AKT-mTOR pathway activation. The mTOR pathway was also inhibited in human VHL-related PCC cells, however, in an AMPK-independent manner. Metformin-induced decrease of HIF1A levels was likely mediated by proteasomal degradation. Altogether our results suggest that metformin impairs PCC cellular proliferation. Highlights: Metformin reduces rat PC12-Adh cell proliferation through AMPK activation. Metformin impairs AMPK-PI3k-AKT-mTOR pathway activation in rat PC12-Adh cells. Metformin impairs mTOR pathway independently of AMPK in VHL-mutant PCC cells. Metformin regulates HIF1A levels by increasing its proteasomal degradation.